2009
DOI: 10.2176/nmc.49.139
|View full text |Cite
|
Sign up to set email alerts
|

Initial Clinical Experience of Vasodilatory Effect of Intra-cisternal Infusion of Magnesium Sulfate for the Treatment of Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage

Abstract: The vasodilatory effect of intra-cisternal infusion of magnesium sulfate solution was evaluated in 10 patients with symptomatic vasospasm after aneurysmal subarachnoid hemorrhage (SAH) who underwent early clipping surgery. Cisternal drainage was installed in the prepontine and/or sylvian fissures. Carotid angiography was performed immediately after the onset of symptomatic vasospasm, then intracisternal infusion of 15 mmol/l magnesium sulfate in Ringer solution was started at 20 ml/hr and continued until day 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The mean Evans index after the injection (25.2 AE 2.0%) did not change compared to before injection. MR imaging did not show any pathological findings except for hydrocephalus after intracisternal injection of MgSO 4 . Figure 2 shows the temporal changes of cerebral artery diameters.…”
Section: Temporal Profile Of Neuroimaging Changesmentioning
confidence: 81%
See 1 more Smart Citation
“…The mean Evans index after the injection (25.2 AE 2.0%) did not change compared to before injection. MR imaging did not show any pathological findings except for hydrocephalus after intracisternal injection of MgSO 4 . Figure 2 shows the temporal changes of cerebral artery diameters.…”
Section: Temporal Profile Of Neuroimaging Changesmentioning
confidence: 81%
“…We previously found that intracisternal infusion of MgSO 4 solution improved reduced cerebral blood flow after experimental SAH in rats using a quantitative autoradiographic method [2], and that intracisternal injection of MgSO 4 solution dilated the spastic cerebral arteries in the canine experimental SAH model using angiography [3]. Recently, we reported the first clinical application of intracisternal infusion of MgSO 4 solution for the treatment of symptomatic cerebral vasospasm after aneurysmal SAH and demonstrated the vasodilatory effect on the spastic arteries [4]. However, optimal duration of the vasodilatory effect and optimal Mg 2+ concentration in the CSF remain unclear, although the effect of CSF Mg 2+ concentration on cat normal arterioles was dose dependent and caused dilation in the range of 2.4-9.6 mEq/l [6].…”
Section: Introductionmentioning
confidence: 99%
“…Direct intracisternal infusion overcomes the problem of peripheral toxicity and may achieve a cerebrospinal fluid magnesium level sufficient to reverse cerebral vasospasm and augment its neuroprotective effects. 24 Another possible explanation of the lack of action could be the inability to provide neuroprotection for early brain injury with the current time window of administration. Whether earlier administration within the first 2 hours, like in the ongoing FAST_MAG Trial (Field Administration of Stroke Therapy-Magnesium Phase 3 Clinical Trial http://www.fastmag.info/index.htm), remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…These concentrations cannot be produced by an intravenous administration of magnesium sulfate since the systemic side effects could be hazardous. Mori et al administered magnesium sulfate via a cisternal catheter in patients with cerebral vasospasm refractory to other forms of therapy and found a reduction of the extent of arterial narrowing [79], measured by transcranial Doppler sonography.…”
Section: Intrathecal Delivery Of Vasodilatorsmentioning
confidence: 99%